2020
DOI: 10.1530/jme-19-0198
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-146b-5p via iodine involvement repressed papillary thyroid carcinoma cell proliferation

Abstract: miR-146b-5p is overexpressed in papillary thyroid carcinoma (PTC) and is thought to be a related diagnostic marker. Previous studies have indicated the effects of iodine on oncogenic activation. However, the effect of iodine on the proliferation of PTC cells and the associated underlying mechanisms remain unclear. We found that miR-146b-5p was downregulated and smad4 was upregulated in patients exposed to high iodine concentration by in situ hybridisation (ISH) and immunohistochemical (IHC). NaI (10-3 M) treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that miR-146b is related to the occurrence, development, proliferation, invasion, and metastasis of thyroid cancer (19)(20)(21). Several reports have confirmed miR-146b to be highly expressed in patients with a high risk of BRAF V600E mutations and advanced PTC (P = 0.001), suggesting that miR-146b is a marker of recurrence or metastasis in PTC patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that miR-146b is related to the occurrence, development, proliferation, invasion, and metastasis of thyroid cancer (19)(20)(21). Several reports have confirmed miR-146b to be highly expressed in patients with a high risk of BRAF V600E mutations and advanced PTC (P = 0.001), suggesting that miR-146b is a marker of recurrence or metastasis in PTC patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overexpression of miR-146b-5p promoted the proliferation, migration, and invasion of HT29 and SW620 cells, while its inhibition suppressed the proliferation, migration, and invasion of CRC cells. miR-146b-5p is expressed in most human organs and serves important roles in numerous diseases, including neurodegenerative diseases (33,34), inflammation (35)(36)(37) and tumors (38,39). Wu et al (34) identified differentially expressed miRNAs in peripheral blood of patients with Alzheimer's disease using small RNA sequencing and reported that miR-146b-5p might contribute to this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that transforming growth factor (TGF)-b1 regulates specific miRNAs, such as mir-146b-5p, in normal cells and cancer. Because TGF-b1 also regulates epithelial-mesenchymal transition in PTC, this growth factor has important roles in the expression of specific miRNAs for the progression of thyroid cancer (30)(31)(32). Inactivating miR-146b has been considered as a promising strategy also in thyroid cancer therapy.…”
Section: Discussionmentioning
confidence: 99%